2017
DOI: 10.1073/pnas.1700695114
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation of Pseudomonas aeruginosa from dormancy requires hibernation promoting factor (PA4463) for ribosome preservation

Abstract: Significance The dormant subpopulations of Pseudomonas aeruginosa biofilms are linked to chronic infections because dormant cells tolerate antibiotic treatment and then repopulate the infections when conditions become favorable. Dormant cells must maintain cellular integrity, including preformed ribosomes, to resuscitate. The small-ribosome–binding proteins, ribosome modulation factor, and hibernation promoting factor (HPF) have evolved to maintain ribosomes in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
82
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 49 publications
11
82
2
1
Order By: Relevance
“…Our prior transcriptomics analyses of P. aeruginosa biofilm subpopulations showed high abundance of mRNA encoding the HPF, in the dormant antibiotic‐tolerant subpopulation of cells (Williamson et al, ). A deletion of the hpf gene resulted in impaired recovery of starvation‐induced dormant cells, as well as loss of ribosomal RNAs in the starved cells (Akiyama et al, ). Those results demonstrated that HPF is required for ribosome protection in the dormant subpopulation of cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior transcriptomics analyses of P. aeruginosa biofilm subpopulations showed high abundance of mRNA encoding the HPF, in the dormant antibiotic‐tolerant subpopulation of cells (Williamson et al, ). A deletion of the hpf gene resulted in impaired recovery of starvation‐induced dormant cells, as well as loss of ribosomal RNAs in the starved cells (Akiyama et al, ). Those results demonstrated that HPF is required for ribosome protection in the dormant subpopulation of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Binding of these factors causes formation of inactive 70S ribosomes, or inactive100S dimers (Vila-Sanjurjo et al, 2004;Kato et al, 2010), with YfiA competing with HPF, and forming an inactive 70S ribosome (Ueta et al, 2005). In P. aeruginosa PAO1, RMF does not appear to be required for recovery from starvation or for ribosome integrity during starvation (Akiyama et al, 2017). P. aeruginosa PAO1 does not encode a YfiA homolog.…”
Section: Introductionmentioning
confidence: 99%
“…The 100S ribosome is ubiquitously found in all bacterial phyla and is important for bacterial survival during nutrient limitation (2-6), antibiotic stress (7), host colonization (8), dark adaptation (9), and biofilm formation (10,11). A common feature of these biological processes is that cells generally conserve energy by undergoing metabolic and translational dormancy because protein synthesis accounts for >50% of energy costs (12,13).…”
mentioning
confidence: 99%
“…A common feature of these biological processes is that cells generally conserve energy by undergoing metabolic and translational dormancy because protein synthesis accounts for >50% of energy costs (12,13). The dimerization of 70S ribosomes has been shown to down-regulate translational efficiency in vivo (3) and in vitro (3,14), and bacteria lacking 100S ribosomes are prone to early cell death concomitant with rapid ribosome degradation (3,10,15,16). These studies lead to a model whereby the formation of the 100S complex sequesters the ribosome pool away from active translation, and 70S self-dimerization prevents ribosome degradation by an unknown pathway (3,17).…”
mentioning
confidence: 99%
“…exponential phase of growth) have higher ribosome content than bacteria under growth-limiting conditions (i.e. stationary phase of growth; low nutrient conditions) (Nomura et al, 1984;Beste et al, 2005;Perez-Osorio et al, 2010;Akiyama et al, 2017). Additionally, the translational elongation rate and the number of active ribosomes decrease drastically during slow growth (Dai et al, 2016).…”
mentioning
confidence: 99%